2020
DOI: 10.3390/agronomy10020220
|View full text |Cite
|
Sign up to set email alerts
|

A Composite Bioinoculant Based on the Combined Application of Beneficial Bacteria and Fungi

Abstract: A composite soil bioinoculant containing beneficial bacteria and fungi was developed for biocontrol of plant pathogens, phosphorous mobilization, stem degradation, humification, and nitrogen fixation. A Trichoderma asperellum isolate with outstanding in vitro antagonistic abilities toward a series of plant pathogenic fungi was included as a potential biocontrol component. The selected strain was also shown to promote growth and increase photosynthetic activity of tomato plants. For phosphorous mobilization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In this study, the plant growth-promoting capacity of a new species, T. aggressivum f. europaeum, which is characterised by its rapid growth and sporulation, was analysed and compared to that of T. saturnisporum, a species characterised as a plant-growth promoter by Diánez et al [16,18]. Although Allaga et al [35] recommend not using species that produce green mould disease, these species do not create any problems in horticultural crops or pose any danger to mushroom crops, as long as they are applied in different geographical areas. Additionally, mushrooms are produced in closed locations and under completely different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the plant growth-promoting capacity of a new species, T. aggressivum f. europaeum, which is characterised by its rapid growth and sporulation, was analysed and compared to that of T. saturnisporum, a species characterised as a plant-growth promoter by Diánez et al [16,18]. Although Allaga et al [35] recommend not using species that produce green mould disease, these species do not create any problems in horticultural crops or pose any danger to mushroom crops, as long as they are applied in different geographical areas. Additionally, mushrooms are produced in closed locations and under completely different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also demonstrated that the four tested biostimulants triggered shoot and root biomass production compared to untreated control. The dual beneficial effect was also recorded on tomato, since Allaga et al [26] reported that a composite bioinoculant containing beneficial fungi and bacteria (Trichoderma, Azotobacter and Streptomyces) was an efficient biocontrol agent, as well as an efficient biostimulant able to improve growth and photosynthetic activity of tomato.…”
Section: The Role Of Non-microbial and Microbial Biostimulants In Mormentioning
confidence: 97%
“…Optimizing the fermentation process in view of reassembling strains with differing modes of action into small communities, thereby providing more consistent protection or growth promotion than with the application of single strains, is a challenging goal worthy to venture as such strategy could widen the application of bioproducts [140,141]. Further development of the fermentation strategies for biofertilizer production should also be focused on products able to manipulate and control phyto-microbiome structure [142], which will be the next biotechnological approach in the Sustainable Agriculture.…”
Section: Perspective Developments and Conclusionmentioning
confidence: 99%